Effect of a course on educational tools on students’ attitude and digital literacy skills - Samani, Ebrahim; Bagheripour, Raziyeh; Noordin, Nooreen (Scientific Publishing Institute, 2020)
This paper aimed at evaluating the effect of a course on educational tools on the participants’ digital literacy and collecting information on their attitude toward these tools and their pedagogical use as the result of attendance in this course. There were 15 participants in this study who attended the one-month course in one of the charity summer schools in Bam, Iran. The content of the course included topics like tagging, cyber threats, presentation tools, back up, creating video clips and so forth. Analysis of the results showed that there was a significant difference in digital literacy scores and attitudes of students between pre and posttests. A review of the participants’ projects and activities in Edublogs demonstrated that the participants were able to easily adapt technologies in creating different artifacts. The findings of this study provide insight to educators in their task of increasing digital literacy in not only society but also among students.